On the border of some correspondences: Teresa Lodi in Florence after World War II among papyri, manuscripts and ancient books - Francesca Aiello; Simona Inserra (Bibliothecae.it, 2023)
The paper intends to deepen, through the study of published and unpublished correspondence and through the analysis of the relationships with some librarians and scholars of the time, the role of Teresa Lodi (1889-1971), librarian and director of the Laurentian Library. In particular, the management of purchases, the conservation and the use of papyrus and parchment materials and books in general are analysed.